Impacts of rural road on household welfare in Vietnam: Evidence from a replication study - Cuong Viet Nguyen (Kiel Institute for the World Economy (IfW), 2016)
Recently, there is a call for replication research to validate empirical findings, especially findings important for development policies. Thus, this study tried to replicate estimation results from Mu and van de Walle ("Rural Roads and Local Market Development in Vietnam" published in Journal of Development Studies 2011). Overall, the author is able to replicate the most estimates from Mu and van de Walle. He finds the positive effect of rural road on local market development. In addition to the pure replication, the author also estimates the effect of the road project on additional outcomes including access to credit and migration, but do not find significant effects on these outcomes.
Keywords: H43; O12; C14; 330; replication; impact; evaluation; propensity; score; matching; rural; road; Vietnam